The Effect of Organizational Characteristics on the Appointment of Nonfamily Managers in Private Family Firms: The Moderating Role of Socioemotional Wealth. (June 2015) - Vandekerkhof, Pieter; Steijvers, Tensie; Hendriks, Walter; Voordeckers, Wim
This article examines the effect of organizational characteristics (firm innovativeness, firm internationalization, firm size) on the appointment of nonfamily managers in private family firms while taking into account the moderating role of socioemotional wealth (SEW). While these organizational characteristics increase the need for expertise, family firms cope with a limited pool of family managers. Therefore, new creative knowledge from nonfamily managers is needed. However, results from a sample of 145 Belgian family firms indicate that the positive effect of organizational characteristics on the integration of nonfamily managers decreases when family-related objectives reflected by SEW become more important for the firm.